Estimating the direction of arrival of the multipath radio signal using Capon technique / Haslinah Ruslan - Ruslan, Haslinah (1996)
One of the aim of array signal processing is to extract useful characteristic of the incident signal(s) field such as the Direction Of Arrival (BOA). The radio signals incident on the array are considered as plane waves, narrowband and may reach the array via multipath propagation such as reflection, refraction and diffraction occurs in outdoor and indoor environment From the previous project [19], the used of Barttett Beamforming technique in DOA estimation using uniform linear and planar array were presented. However, it has limited resolution in resolving two closely space signal. To overcome the problem, Capon method is introduced. Capon method provides high resolution estimation of the DOA of the multipath radio signals. The comparison of performance between Bartlett Beamforming and Capon technique in DOA estimation based on actual measured data is presented. The data were captured using the synthetic planar array antenna in a typical outdoor environment where the received signal frequency is centered at 870 MHz. C++ programming language was used to develope the Capon algorithm.